Thomas King works and impact - Gruber, Eva (Boydell & Brewer, 2012)
Thomas King is one of North America's foremost Native writers, best known for his novels, including 'Green Grass, Running Water', for the 'DreadfulWater' mysteries, and for collections of short stories such as 'One Good Story, That One' and 'A Short History of Indians in Canada.' But King is also a poet, a literary and cultural critic, and a noted filmmaker, photographer, and scriptwriter and performer for radio. His career and oeuvre have been validated by literary awards and by the inclusion of his writing in college and university curricula. Critical responses to King's work have been abundant, yet most of this criticism consists of journal articles, and to date only one book-length study of his work exists. 'Thomas King: Works and Impact' fills this gap by providing an up-to-date, comprehensive overview of all major aspects of King's oeuvre as well as its reception and influence. It brings together expert scholars to discuss King's role in and impact on Native literature and to offer in-depth analyses of his multifaceted body of work. The volume will be of interest to students and scholars of literature, English, and Native American studies, and to King aficionados. Contributors: Jesse Rae Archibald-Barber, Julia Breitbach, Stuart Christie, James H. Cox, Marta Dvorak, Floyd Favel, Kathleen Flaherty, Aloys Fleischmann, Marlene Goldman, Eva Gruber, Helen Hoy, Renée Hulan and Linda Warley, Carter Meland, Reingard M. Nischik, Robin Ridington, Suzanne Rintoul, Katja Sarkowsky, Blanca Schorcht, Mark Shackleton, Martin Kuester and Marco Ulm, Doris Wolf. Eva Gruber is Assistant Professor in the Department of American Studies at the University of Constance, Germany